Efecto del tratamiento de la anemia por deficiencia de hierro en el embarazo y en el posparto en gestantes de un hospital público de Loreto 2022 - Calderon Galloza, Maria Cristina del Pilar (2025)
GENERAL OBJECTIVE: To evaluate the effect of the treatment of iron deficiency anemia in pregnancy and postpartum in pregnant women in a public hospital in Loreto 2022. MATERIALS AND METHODS: A quantitative study will be carried out, according to the intervention of the descriptive researcher according to the scope to demonstrate a causal relationship: analytical, according to the number of measurements of the cross-sectional study variable and according to the planning of the data collection: retrospectivo. The study population will consist of all pregnant women diagnosed with anemia in the period of one year-2022 and a sample of 323 patients. A nationally validated form will be used to collect data and measure study variables. CONCLUSIONS: Treatment for anemia during pregnancy and postpartum impacts the level of hemoglobin and hematocrit of pregnant women.